Inflammatory osteoarthritis which was precipitated by Arimidex and resolved with tamoxifen. (2nd November 2010) - Williams, Stella; Michael, Benedict; Mewar, Devesh; Tunn, Edward
Abstract : We report the case of a 51-year-old woman who presented with an inflammatory flare of osteoarthritis of the small joints of her hands occurring in a temporal relationship with the commencement of Arimidex, prescribed to reduce systemic oestrogen levels to treat breast cancer. Following the cessation of Arimidex and the initiation of tamoxifen, a specific oestrogen receptor antagonist, this flare resolved. It has long been observed that during the menopause, as oestrogen levels decline, many women develop osteoarthritis or experience progression of the disease. However, this theory of oestrogen-dependent osteoarthritis has not been consistently demonstrated in animal models. As far as the authors are aware, this is the first case in which systemic oestrogen reduction has resulted in a severe osteoarthritis flare but targeted oestrogen receptor blockade led to a resolution of symptoms. These findings may inform the pathophysiological process underlying oestrogen-dependent osteoarthritis, although further series are needed.